2010
DOI: 10.1088/2040-8978/12/3/035209
|View full text |Cite
|
Sign up to set email alerts
|

Optical switching in hybrid semiconductor nonlinear photonic crystal slabs with Kerr materials

Abstract: Nonlinear photonic crystals, whose refractive index distribution can be tuned optically, have been used to demonstrate all-optical switching due to a change of the refractive index and subsequent shift of the bandgap edge or the defect state resonant frequency. Semiconductor-based all-optical switching is still limited by the weak nonlinearity and the slow response time owing to the slow dynamics of two-photon-generated free carriers. Here we introduce a concept of hybrid nonlinear photonic crystals that are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…This change is quantified by the expression n ′ a = n a + n 3 I pump where n 3 is the Kerr nonlinearity constant and has the value n 3 = 1.15 × 10 −12 cm 2 /W for polystyrene. 10 For the pump field intensity I pump = 31.0 GW/cm 2 we found that the photonic crystal band edge shifts such that ∆ε v = − 17.32 meV. This means that the hybrid system can be used to study the nonlinear properties of photonic crystals.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…This change is quantified by the expression n ′ a = n a + n 3 I pump where n 3 is the Kerr nonlinearity constant and has the value n 3 = 1.15 × 10 −12 cm 2 /W for polystyrene. 10 For the pump field intensity I pump = 31.0 GW/cm 2 we found that the photonic crystal band edge shifts such that ∆ε v = − 17.32 meV. This means that the hybrid system can be used to study the nonlinear properties of photonic crystals.…”
Section: Resultsmentioning
confidence: 79%
“…Applications for photonic crystals include all-optical microchips for optical information processing, optical communication networks, sensors, and solar energy harvesting. [7][8][9][10][11][12] In our investigation, we consider a nonlinear photonic crystal, which has a refractive index distribution that can be tuned optically. The nonlinear photonic crystal surrounds the hybrid system and is used to manipulate the interaction between the quantum emitter and graphene nanodisk.…”
Section: Introductionmentioning
confidence: 99%
“…It takes advantage of the high-index contrast of silicon and superior optical nonlinearity of polystyrene, and ease of integration with other silicon optical devices. 68 The key point in fabricating this semiconductor-polymer compound NPC lies in how to uniformly and densely ll polymers into the small air holes with a diameter of only hundreds of nanometers. Previously, several techniques have been employed for the inltration of PCs with organic composites.…”
Section: Silicon-polystyrene Hybrid Nonlinear Photonic Crystalsmentioning
confidence: 99%
“…Another type of hybrid structure, namely slab PC with air holes infiltrated with polymer materials, has been proposed and analyzed theoretically in our previous works [26,27], and the bandgap and cavity mode shift under external pump light have been investigated. The resulting photonic crystal is a hybrid slab structure, which can be made by infiltrating organic polymer materials into the void space of the pillar array.…”
Section: Introductionmentioning
confidence: 99%